2019
DOI: 10.1038/s41598-019-53491-w
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic and Macro-Porous Carbon Nano-foam Electrodes with Improved Mass Transport for Vanadium Redox Flow Batteries

Abstract: Although free-standing sheets of multiwalled carbon nanotubes (MWCNT) can provide interesting electrochemical and physical properties as electrodes for redox flow batteries, the full potential of this class of materials has not been accessible as of yet. The conventional fabrication methods produce sheets with micro-porous and meso-porous structures, which significantly resist mass transport of the electrolyte during high-current flow-cell operation. Herein, we developed a method to fabricate high performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…[ 32–35 ] Advanced numerical simulations on porous media have demonstrated that streamwise‐oriented fibers and pores can lead to increased permeabilities and improved dispersion efficiency; [ 36 ] furthermore, material sets possessing wide variability in pore sizes with high specific surface area induce higher dispersion and reaction rates, improving overall performance. [ 37–41 ] Collectively, these prior works constitute important advances in the electrochemical science and engineering of porous electrodes. However, translation beyond the lab‐scale remains a concern, as constraints inherent to existent large‐scale carbon fiber manufacturing processes necessitate the introduction of additional and often complex post‐treatments to produce electrodes with suitable performance characteristics, which results in increased production costs.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 32–35 ] Advanced numerical simulations on porous media have demonstrated that streamwise‐oriented fibers and pores can lead to increased permeabilities and improved dispersion efficiency; [ 36 ] furthermore, material sets possessing wide variability in pore sizes with high specific surface area induce higher dispersion and reaction rates, improving overall performance. [ 37–41 ] Collectively, these prior works constitute important advances in the electrochemical science and engineering of porous electrodes. However, translation beyond the lab‐scale remains a concern, as constraints inherent to existent large‐scale carbon fiber manufacturing processes necessitate the introduction of additional and often complex post‐treatments to produce electrodes with suitable performance characteristics, which results in increased production costs.…”
Section: Figurementioning
confidence: 99%
“…[32][33][34][35] Advanced numerical simulations on porous media have demonstrated that streamwise-oriented fibers and pores can lead to increased permeabilities and improved dispersion efficiency; [36] furthermore, material sets possessing wide variability in pore sizes with high specific surface area induce higher dispersion and reaction rates, improving overall performance. [37][38][39][40][41] Collectively, these prior works constitute important advances in the electrochemical science and engineering of porous electrodes. However, translation beyond the Figure 1.…”
mentioning
confidence: 99%
“…[13][14][15] The large surface area introduced by chemical treatment and the deposition of carbon nanomaterials are also enhanced reaction points for the vanadium species on the electrodes. [22][23][24][25][26][27][28][29] In recent research, the optimal combination of thermally activated and nonactivated carbon felts in VO 2+ /VO 2 + and V 2+ /V 3+ redox couples showed the most efficient configuration. 31 The electron transfer was found to occur by an inner-sphere process in VO 2+ /VO 2 + redox couple, whereas redox reaction of V 2+ /V 3+ progressed an outer-sphere electron transfer.…”
Section: Chemical Activationsmentioning
confidence: 99%
“…15 With some of metal and metal oxide additions, the chemical stability of the electrode surface remains poor, and the introduction is not inexpensive. Carbon-based nanostructured materials include carbon nanofibers (CNFs), 22 carbon nanotubes (CNTs), [23][24][25][26] and graphene (graphene oxide, nanowalls), 27,28 carbon nanosheets and nanorods. 29 These modification, deposition and growth techniques with carbon nanomaterials introduce enhanced wettability, a much larger surface area, and higher conductivity for vanadium RFBs.…”
Section: Chemical Activationsmentioning
confidence: 99%
“…e secondary particles formed from agglomeration of the primary particles were random in size and ranged between 100 and 200 nm indicating that the crystals of the phosphor-olivine LiFe 0.5 Mn 0.5 PO 4 grow very well and have interparticle boundaries that have an effect in the chemistry of the material and its reactivity due to its porous nature, whereas the LiFe 0.5 Mn 0.5 PO 4 -MWCNT composite cathode shown in Figure 3(e) revealed nanoclusters of long-stranded carbon nanotubes which facilitate the movement of electrons during extraction and insertion of lithium within 3D framework between nanotubes and adjacent LiFe 0.5 Mn 0.5 PO 4 particles. e porous nanostructure of the LiFe 0.5 Mn 0.5 PO 4 is lamented by the carbon nanotubes, providing a larger electrode surface area, reducing the energy loss due to both activation and concentration of polarizations at the electrode surface [32]. e synthesized LiFe 0.5 Mn 0.5 PO 4 particles were subsequently attached to the ends and walls on the nanotubes.…”
Section: Morphology and Structural Characterizationmentioning
confidence: 99%